Pendampingan TOEFL Dengan Metode Partisipasi Masyarakat Untuk Mencapai Nilai Ideal Di Masa Pandemi - Indah Azhari; Nabila Senja Wahyuningtias; Rizky Tri Demarwan; Fatan Fakihardi (Health Community Engagement, 2021)
TOEFL training with the Cooperative Integrated Reading and Composition method aims to help lecturers and students at several universities in West Nusa Tenggara to increase the TOEFL (Test of English as a foreign language) score during the pandemic. The difficulty of determining the correct method and media during a pandemic for students and lecturers to achieve the ideal TOEFL is the main reason for carrying out this community service. This community service aims to provide knowledge and readiness to face the TOEFL (Test of English as Foreign Language). For students and lecturers in West Nusa Tenggara. This community service is carried out online using zoom technology as a learning medium for one month. The target community is the campus community, students and lecturers from various universities in West Nusa Tenggara. The method used in this community service is the Cooperative Integrated Reading and Composition (CIRC) method, where participants are divided into several groups, then given tips and strategies in answering the TOEFL test. Each group discussed and exchanged ideas in answering all the questions in the TOEFL. The cost of this community service activity is entirely sourced from the service implementation team. After implementing this community service activity, participants have the ability and readiness and a quite significant value than before. This can be proven by the results of the Post Test Participants after participating in the training showed very positive changes. Keywords: CIRC, covid-19, ideal value, TOEFL training